Advanced medical monitoring for the battlefield: A review on clinical applicability of compensatory reserve measurements for early and accurate hemorrhage detection. (8th August 2022) - Convertino, Victor A.; Cardin, Sylvain
Abstract : This report provides military medical caregivers with the latest clinical verification for use of arterial waveform analysis as a monitoring tool for early detection of hemorrhage with superior accuracy compared to standard vital signs addressing CDID and SOCOM capability gaps. Abstract : ABSTRACT: Hemorrhagic shock remains the leading cause of mortality in civilian trauma and battlefield settings. The ability of combat medics and other military medical personnel to obtain early identification and assessment of a bleeding casualty is hampered by the use of standard vital signs that fail to provide early predictive indicators of the onset of shock because of compensatory mechanisms. Over the past decade, the emergence and application of new technologies that incorporate the use of artificial intelligence have revealed that continuous, real-time arterial waveform analysis (AWFA) reflects the recruitment of such compensatory mechanism. As such, AWFA can provide early hemorrhage detection and indication of the onset of overt shock compared with standard vital signs. In this review, we provide for the first time a summary of clinical data collected in patients with varying conditions of blood loss, sepsis, and resuscitation with direct comparison of AWFA and standard vital signs. Receiver operating characteristic area under the curve data clearly demonstrate that AWFA provides greater accuracy with early indicators for changes in blood volume compared with standard vital signs. A consistently greater sensitivity generated by AWFA compared with vital signs is associated with its ability to provide earlier hemorrhage detection, while higher specificity reflects its propensity to distinguish "poor" compensators (i.e., those with relatively low tolerance to blood loss) from "good" compensators. The data presented in this review demonstrate that integration of AWFA into medical monitoring capabilities has the potential to improve clinical outcomes of casualties by providing earlier and individualized assessment of blood loss and resuscitation. Abstract :